Emotional Intelligence as an Educational Management Tool to Enhance Student Leadership from Economic-Administrative and Technical Areas - Del Pino Peña, Rebeca; Aguilar Fernández, María de los Ángeles (Cuadernos de Administración, 2013)
Educational management focuses on improving all educational and administrative processes of education institutions through a comprehensive training proposal that provides students with tools to meet the challenges of the organizational dynamics of the 21st century. Thus, is how currently various emotional education programs seek to strengthen student leadership so they can have solid academic performance in the classroom and successful professional development in current occupational settings. Given this background, this ex-post-facto cross-sectional descriptive type study was frameworked on identifying differences among the perception of emotions, managing one’s emotions, managing emotions of others, and on using emotions of students from educational programs of economic-administrative and technical baccalaureate degree and education institutions of the public sector in Mexico, to lay the foundation to guide a series of educational management actions based on the emotional training of students to enhance their  school and professional leadership. Among the main results obtained in this study, statistically significant differences were detected in the study variables, which shows the need for educational managers to undertake the planning and implementation of emotional training processes with the insertion emotional intelligence curriculum in student training; mainly, in the economic and administrative areas, who have the greatest areas of opportunity in this regard, so that they can project sound leadership in their studies and in their future professional work, which could contribute to organizations keeping up with market demands and the globalization of the current economy.